Strategi Komunikasi Sindiran Konten Lip Service TikTok @podcastkeselaje - Simatupang, Gloria Maranatha N.; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study analyzes the communication strategies employed in the satirical content of Lip Service, popularized by Oza Rangkuti on TikTok. Using a qualitative approach, this study explores the use of satirical humor as a tool for delivering social criticism and entertainment. Data was collected through in-depth interviews, content observation, and analysis of three videos with high levels of interaction. The results indicate that subtle satire combined with humor serves to both entertain the audience and convey a message. Humor is used to reduce audience resistance to criticism, enhance content appeal, and improve message retention. Additionally, Oza incorporates nonverbal communication in the form of visual expressions and distinctive gestures to enrich the entertainment element, creating a unique and relatable viewing experience for the audience. The content also utilizes relevant social issues to build emotional connections with the audience, encouraging active interaction and opening up spaces for discussion. This study highlights how satirical communication strategies can address sensitive issues in an entertaining yet meaningful way. The study contributes to a new understanding of satirical humor as a strategic approach in digital communication. Penelitian ini menganalisis strategi komunikasi dalam konten sindiran Lip Service yang dipopulerkan oleh Oza Rangkuti di TikTok. Dengan menggunakan pendekatan kualitatif, studi ini mengeksplorasi penggunaan humor sindiran sebagai alat penyampaian kritik sosial dan hiburan. Data diperoleh melalui wawancara mendalam, observasi konten, dan analisis tiga video dengan tingkat interaksi tinggi. Hasil penelitian menunjukkan bahwa sindiran halus dipadukan dengan humor yang berperan untuk menciptakan hiburan bagi audien sekaligus dalam menyampaikan pesan. Humor digunakan untuk mengurangi resistensi audiens terhadap kritik, memperkuat daya tarik konten, dan meningkatkan daya ingat pesan. Selain itu, Oza menggabungkan komunikasi non-verbal dalam bentuk ekspresi visual dan gestur khas untuk memperkaya elemen hiburan, menciptakan pengalaman menonton yang unik dan relatable bagi audiens. Konten ini juga menggunakan isu sosial yang relevan untuk membangun keterhubungan emosional dengan audiens, mendorong interaksi aktif, serta membuka ruang diskusi. Penelitian ini menyoroti bagaimana strategi komunikasi dalam bentuk sindiran dapat mengangkat isu sensitif secara menghibur namun tetap bermakna. Studi ini berkontribusi pada pemahaman baru tentang humor sindiran sebagai pendekatan strategis dalam komunikasi digital.